Integrated Model to Describe Morphine Pharmacokinetics in Humans. (6th March 2019) - Liu, Tao; Ivaturi, Vijay; Gobburu, Jogarao
Abstract: The pharmacokinetics (PK) of morphine has been extensively investigated. Though different publications have focused on the various aspects of morphine PK, none have quantitatively interpreted morphine PK across different publications. The objective of this research is to summarize the current understanding of morphine PK in humans quantitatively. In this research, a parent‐metabolite compartmental PK modeling approach was used to summarize the current understanding of morphine PK in humans. Plasma concentration‐time profiles and cumulative urine recovery time profiles of morphine, morphine‐3‐glucuronide, and morphine‐6‐glucuronide were digitized from the previous publications to develop the parent‐metabolite PK model. The parent‐metabolite PK model successfully described the plasma concentration‐time profiles and cumulative urine recovery of morphine as well as its two major metabolites, morphine‐3‐glucuronide and morphine‐6‐glucuronide, after intravenous and oral administration of morphine. This research separated out the first‐pass effect on morphine metabolism after oral administration. By integrating these results with two mass balance studies of morphine, a clear picture of morphine absorption and disposition is given. Though the results are mainly based on data collected from healthy volunteers or patients whose disease is not expected to impact morphine PK, the parent‐metabolite model sets a framework to further evaluate morphine PK in special populations, such as pediatrics and patients with renal impairment.